2014
DOI: 10.1155/2014/870864
|View full text |Cite
|
Sign up to set email alerts
|

Agromorphological Traits Variability of the Ethiopian Lentil and Exotic Genotypes

Abstract: Understanding the genetic relationships and diversity of Ethiopian lentil in relation to lentil from other countries is important in attempting to widen the genetic base of germplasm in the country. The objectives of this study were to generate information on agromorphological variability, to estimate PCV, GCV, heritability, and expected genetic advance of quantitative traits of lentil. 228 genotypes with different population types were studied for 11 agromorphological traits and rust disease severity score fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The presence of high heritability coupled with high-expected genetic advance indicated predominance of additive gene action in the expression of these characters and consequently greater chance of improving these traits through simple selection. These results are in conformity with the findings of Mekonnen et al (2014) for 100-seed weight and seed yield.…”
Section: Resultssupporting
confidence: 92%
“…The presence of high heritability coupled with high-expected genetic advance indicated predominance of additive gene action in the expression of these characters and consequently greater chance of improving these traits through simple selection. These results are in conformity with the findings of Mekonnen et al (2014) for 100-seed weight and seed yield.…”
Section: Resultssupporting
confidence: 92%
“…Cluster analysis grouped the 29 slender leaf accessions into seven supported clusters based on the level of variation among the accessions. A similar strategy was applied by Zhang et al [30] and Mekonnen et al [31] on the agro-morphological characterization of Cucumis melo and lentils accessions, respectively. Diversity within supported clusters ranged from 0% (for singletons) to 45.07% as observed in Cluster 7. e high morphological diversity indicates a high potential of phenotypic selection which is a desirable aspect to plant breeders.…”
Section: Discussionmentioning
confidence: 99%
“…. Abo-Hegazy et al [29], Mekonnen et al [30] and Sharma et al [31] reported 100 seed weight and pod plant -1 having a positive direct effect on yield plant -1 . on the contrary number of seeds pod -1 (-0.066), secondary branches plant -1 (-0.056), plant height (-0.042) and days to 50% flowering (-0.020) showed negative direct effect at genotypic level with yield plant -1 similar to that observed by Pandey et al [32].…”
Section: Resultsmentioning
confidence: 99%